Deformation and exhumation of the Ronda peridotite (Spain). Issue 4 (4th August 2013) - Précigout, Jacques; Gueydan, Frédéric; Garrido, Carlos J.; Cogné, Nathan; Booth‐Rea, Guillermo
<x xml:space="preserve">Abstract</x> [1] The Ronda peridotite supplies one of the best objects to document subcontinental mantle deformation, but its internal deformation and exhumation mechanisms remain controversial. Here we provide new structural data and numerical results that constrain the Oligocene‐Miocene deformation history of the Ronda massif. We first describe a mantle shear zone in the northern massif that developed subcrustal strain localization during decompression and related partial melting. The deformation regime of this mantle shear zone evolved from penetrative NE‐SW stretching to sinistral shear highlighted by discrete shear bands. We then show structural observations that document a viscous deformation in the southern massif occurring prior to the thrust‐assisted emplacement of the peridotite during large decompression. Finally, we performed numerical investigations that quantify a high temperature of 980°C for the basal peridotite lens at the time of its crustal emplacement. Our numerical results constrain the timing of ductile deformation of the peridotite just before 22 Ma, probably between 30 and 22 Ma. Altogether, these features led us to conclude that the deformation and exhumation of the Ronda peridotite results from lithosphere thinning subsequently inverted in the course of the Oligocene‐Miocene. Among available models, our findings support the hypothesis of peridotite exhumation by the inversion of a thinned back‐arc continental lithosphere during westward slab rollback through the Alboran region.